Bone marrow derived mesenchymal stem cells transplantation rescues premature ovarian insufficiency induced by chemotherapy. (3rd April 2018) - Bao, Riqiang; Xu, Ping; Wang, Yishu; Wang, Jing; Xiao, Li; Li, Gang; Zhang, Chunping
Abstract: Premature ovarian insufficiency (POI) is an important cause of infertility and also cause menopausal symptoms, which greatly reduced the quality of life for women. Hormone replacement therapy (HRT), as an important strategy, improved the quality of life for patients, however, the role of HRT in promoting fertility remains controversial. Therefore, seeking an optimal regime for POI becomes more urgent. In this study, we established POI model induced by CTX and BUS and utilized bone marrow derived mesenchymal stem cells (BM-MSCs) transplantation to treat the POI. We found that the decrease of estrogen and the increase of FSH induced by administration of CTX and BUS were rescued by BM-MSC transplantation. H&E staining and TUNEL assay showed that there were more healthy ovarian follicles and less apoptosis of ovarian cells after treatment with BM-MSCs. Further studies showed that there was an obvious decrease of Bax, p53, and p21 after transplantation, however, CyclinD2 was increased. In conclusion, our results demonstrated that BM-MSCs could restore injured ovarian function. Inhibiting apoptosis and promoting residual ovarian cell proliferation may contribute to the process.